Mechanistic insights into silica nanoparticle–allergen interactions on antigen presenting cell function in the context of allergic reactions. Issue 5 (11th January 2023) - Johnson, Litty; Aglas, Lorenz; Punz, Benjamin; Dang, Hieu-Hoa; Christ, Constantin; Pointner, Lisa; Wenger, Mario; Hofstaetter, Norbert; Hofer, Sabine; Geppert, Mark; Andosch, Ancuela; Ferreira, Fatima; et al.
Abstract : Impact of SiO2 NP-allergen interaction on dendritic cell function altering the immune response, eventually resulting in a harmless, beneficial outcome in terms of allergic reactivity. Abstract : The incorporation of nanomaterials into consumer products has substantially increased in recent years, raising concerns about their safety. The inherent physicochemical properties of nanoparticles allow them to cross epithelial barriers and gain access to immunocompetent cells. Nanoparticles in cosmetic products can potentially interact with environmental allergens, forming a protein corona, and together penetrate through damaged skin. Allergen–nanoparticle interactions may influence the immune response, eventually resulting in an adverse or beneficial outcome in terms of allergic reactivity. This study determines the impact of silica nanoparticle–allergen interactions on allergic sensitization by studying the major molecular mechanisms affecting allergic responses. The major birch pollen allergen Bet v 1 was chosen as a model allergen and the birch pollen extract as a comparator. Key events in immunotoxicity including allergen uptake, processing, presentation, expression of costimulatory molecules and cytokine release were studied in human monocyte-derived dendritic cells. Using an in vivo sensitization model, murine Bet v 1-specific IgG and IgE levels were monitored. Upon the interaction of allergens with silica nanoparticles, we observed an enhanced uptake of the allergen by macropinocytosis, improved proteolytic processing, and presentation concomitant with a propensity to increase allergen-specific IgG2a and decrease IgE antibody levels. Together, these events suggest that upon nanoparticle interactions the immune response is biased towards a type 1 inflammatory profile, characterized by the upregulation of T helper 1 (Th1) cells. In conclusion, the interaction of the birch pollen allergen with silica nanoparticles will not worsen allergic sensitization, a state of type 2-inflammation, but rather seems to decrease it by skewing towards a Th1-dominated immune response.